(untitled) (Bangladesh Agronomy Journal, 2019)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the effect of aqueous extract of sorghum crop residues on weed management and crop performance of wheat. The experiment consisted of three varieties of wheat viz., BARI Gom-19, BARI Gom-21, BARI Gom-24 and five different levels of treatments such as no use of aqueous extract, aqueous extract of sorghum crop residues: 1:20 ratio (w/v), 1:30 ratio (w/v), 1:40 ratio (w/v) and hand weeding. The experiment was laid out in a randomized complete block design with three replications. Seven weed species belonging to five families infested the experimental plots. Weed population, weed dry weight and percent inhibition of weed were significantly influenced by aqueous extract of sorghum crop residues and varieties. The maximum weed growth was noticed with the variety BARI Gom-19 and the minimum was found in the variety BARI Gom-21. The grain yield as well as the other yield contributing characters produced by BARI Gom-21 was the highest among the studied varieties. The highest percent inhibition for all of the weeds was found in hand weeding treatment. The second highest percent weed inhibition was occurred in aqueous extract of sorghum crop residues @ 1:20 ratio (w/v) treatment which was 51.81, 51.10, 52.90, 55.58, 75.27, 73.83 and 53.85 percent for bathua (Chenopodium album), mutha (Cyperus rotundus), durba (Cynodon dactylon), biskatali (Polygonum hydropiper), angta (Paspalum scrobiculatum), tit begun (Solanum torvum) and shama (Echinochloa crusgalli) respectively. The highest loss of grain yield was obtained where no aqueous extract of sorghum crop residues were used. The highest yield and yield attributes were observed where hand weeding is done followed by the application of aqueous extract of sorghum crop residues @1:20 ratio (w/v). Wheat var. BARI Gom-21 with all treatments produced the highest grain and straw yield among the treatment combination. The results of this study indicate that different amount of aqueous extract of sorghum crop residues showed potential activity to suppress weed growth and it has significant effect on the yield of wheat. Therefore, aqueous extract of sorghum crop residues might be used as an alternative way for weed management in effective and sustainable crop production Bangladesh Agron. J. 2018, 21(2): 87-95